Development and preliminary validation of a Chinese Physical Activity Parenting Practices Scale (3–6 years) - Na, Ren; Liang, Ying; Zhang, Haiyue; Yang, Zhe; Li, Nan; Zhang, Wei; Tang, Han; Ye, Weiliang; Zhang, Linyuan; Jiang, Xun; Shang, Lei (Frontiers in Psychology, 2025)
BackgroundThis study aimed to develop a scale to assess the physical activity (PA)-related parenting practices of Chinese parents of children aged 3–6 years based on general parenting theory.MethodsA pool of scale items (123 items) was constructed based on a literature review and in-depth personal interviews. The pretest scale (60 items) was developed using Delphi correspondence and a presurvey. After two rounds of item screening of the pretest scale using exploratory factor analysis (EFA) and analysis of variance, we deleted 30 items. We ultimately developed a formal version of the Chinese Physical Activity Parenting Practices Scale (CPAPPS) using the remaining 30 items. We examined the structure of the scale using factor analysis and evaluated its reliability, validity, and discriminant ability using data from 899 parents of children aged 3–6 years.ResultsThe CPAPPS includes 30 items in 6 dimensions scored on a 5-point Likert scale. The 6 dimensions are education, autonomy promotion, modeling, demands, expectations, and rewards. Both exploratory and confirmatory factor analyses confirmed the construct validity of the scale. Furthermore, the scale had adequate internal consistency, split-half reliability, test–retest reliability, and concurrent validity. Parents younger than 30 scored significantly lower on the demand dimension than parents aged 40–50 (p < 0.05). The differences in rewards and expectations between parents of different ethnicities were statistically significant (p < 0.05). Compared with married parents, parents who were currently single had lower scores for education, rewards, modeling, and autonomy promotion (p < 0.05). There was a significant difference in scores across all dimensions between parents with different places of residence (p < 0.05).ConclusionThe CPAPPS satisfies the conditions for reliability and validity in accordance with psychometric requirements. The scale can be employed to evaluate the characteristics of Chinese parents’ physical activity-related parenting practices and to design family-based PA interventions.